2015
DOI: 10.1093/icesjms/fsv028
|View full text |Cite
|
Sign up to set email alerts
|

Discarding of cod in the Danish Fully Documented Fisheries trials

Abstract: Denmark was the first nation in Europe to promote the use of Fully Documented Fisheries (FDF) through Remote Electronic Monitoring (REM) and CCTV camera systems, with pilot schemes in place since 2008. In theory, such a scheme could supplement and even potentially replace expensive control and monitoring programmes; and when associated with a catch quota management (CQM) system, incentivize positive changes in fishing patterns in a results-based management approach. New data flows are, however, required to ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…The results showed that, on an overall fleet level, there was a tendency for video inspectors to underestimate discards by 32% compared to fishers' discard estimates This supports the findings of Ulrich et al (2015) and van Helmond et al (2015), which suggest that, despite offering a promising way to supplement existing on-board observer control, the REM approach applied in this trial needs some adjustments to optimise video inspector accuracy. This is emphasised by the results obtained when removing all observations where video inspectors commented on the poor quality of the REM data, which showed an overall agreement between fishers and video inspectors on the discard estimates, thus supporting the findings of Stanley et al (2011) and Kindt-Larsen et al (2011).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The results showed that, on an overall fleet level, there was a tendency for video inspectors to underestimate discards by 32% compared to fishers' discard estimates This supports the findings of Ulrich et al (2015) and van Helmond et al (2015), which suggest that, despite offering a promising way to supplement existing on-board observer control, the REM approach applied in this trial needs some adjustments to optimise video inspector accuracy. This is emphasised by the results obtained when removing all observations where video inspectors commented on the poor quality of the REM data, which showed an overall agreement between fishers and video inspectors on the discard estimates, thus supporting the findings of Stanley et al (2011) and Kindt-Larsen et al (2011).…”
Section: Discussionsupporting
confidence: 74%
“…Dalskov and Kindt-Larsen, 2009;Kindt-Larsen et al, 2011;Mangi et al, 2015;Marine Management Organisation, 2013;McElderry et al, 2003;Needle et al, 2015;Ulrich et al, 2015;van Helmond et al, 2015). REM is a full documentation tool that uses closed-circuit-television (CCTV) cameras, GPS and sensors to monitor the fishing operations in-situ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EM trials have been conducted across a variety of industrial fisheries around the world to verify compliance with catch sorting and weighing regulations, discard bans and quota and interaction requirements for protected species, and for full reporting of fishing and on‐board processing mandates (Table ). Trials have shown that EM can provide precise, verifiable, cost‐effective fishery‐dependent data and promote adherence to quota regulations for protected species (Hold et al., ; Needle et al., ; Sylvia, Harte, & Cusack, ; Ulrich et al., ; van Helmond, Chen, & Poos, ). In 2015, the Atlantic pelagic longline fishery became the first US fishery to implement a fleet‐wide EM program to verify the accuracy of bluefin tuna by‐catch (Sylvia et al., ).…”
Section: Current Applications Of Fishery‐dependent Data Technologiesmentioning
confidence: 99%
“…The study period is January 1 2015 to December 31 2016. Over this period, high resolution haul data for five vessels and SIF data could be compared with electronic monitoring (EM) data (GPS) for two vessels, which both had sea-packing equipment and participated in the Danish Cod Catch Quota Management trial (Ulrich et al 2015;Bergsson et al 2017).…”
Section: Study Periodmentioning
confidence: 99%